ADAPTASI SUMBER DAYA MANUSIA TERHADAP PERUBAHAN DIGITAL EKONOMI DI INDONESIA - Najma Khoirin Nisa; Tallana Adyar Kormala; Atina Hidayati (Jurnal Riset Multidisiplin Edukasi, 2026)
The development of the digital economy over the past two decades has transformed industrial structures, business models, and the competency requirements of the workforce in Indonesia. The acceleration of digitalization through e-commerce, fintech, and digital platforms has driven organizations to shift toward more data-driven, automated, and flexible work systems. This transformation requires new competencies, such as digital literacy, data literacy, technology based problem solving skills, and readiness for continuous learning. This study uses a qualitative approach with a systematic literature review method on publications from 2021–2026 to analyze the process of human resource adaptation, supporting and inhibiting factors, and strategies to strengthen workforce readiness. The findings show changes in job structure, marked by a decline in routine tasks and an increase in analytical roles, along with a shift in HR management practices toward digital systems and data-driven decision making. Human resource adaptation is influenced by individual motivation, digital self-efficacy, leadership support, investment in human resource development, and the national digital ecosystem. The main challenges include digital skill gaps, unequal access to training, limited infrastructure, and resistance to change. Therefore, strategies such as reskilling, upskilling, implementation of digital HR, HR analytics, and cross-sector collaboration are needed.